Peligrosa expresión de una estenosis subvalvular aórtica aislada - Prieto Guerra, Maidelis; Blanco Pérez, Yiliam; Cruz Rodríguez, Liz O.; Perdomo Hernández, Héctor D. (CorSalud, 2025)
Peligrosa expresión de una estenosis subvalvular aórtica aislada.